Lessons Learned with a Triad of Stakeholder Advisory Boards: Working with Adolescents, Mothers, and Clinicians to Design the TRUST Study - Alexis Richards; Marissa Raymond-Flesch; Shana D. Hughes; Yinglan Zhou; Kimberly A. Koester (MDPI AG, 2023)
Optimal care for pediatric and adolescent patients is carried out under a triadic engagement model, whereby the patient, caregiver, and clinician work in collaboration. Seeking input from all triad members in the development and implementation of clinical trials and interventions may improve health outcomes for children and adolescents. Sufficient evidence demonstrating how to effectively engage stakeholders from all branches of this triadic model is lacking. We address this gap by describing the successes and challenges our team has encountered while convening advisory groups with adolescent patients, parent stakeholders, and their clinicians to assist in the development and deployment of a technology-based intervention to promote the utilization of sexual and reproductive health services by increasing adolescent-clinician alone-time. Each stakeholder group contributed in unique and complementary ways. Working with advisors, our team aligned the priorities of each group with the goals of the research team. The results were improvements made in the content, design, and delivery of the TRUST intervention. While we were largely successful in the recruitment and engagement of adolescent patients and clinicians, we had less success with parents. Future research will need to explore additional strategies for recruitment and engagement of parents, particularly in rural, minority, and underserved communities.